Diagnosis, occurrence and seed transmission studies of viruses infecting four Centrosema species in Nigeria - Odedara, O.; Hughes, J.; Ayo‐John, E. (Wiley, 2007)
In a survey to detect viruses affecting Centrosema species in two agroecological zones in Nigeria (the derived and northern guinea savanna zones: DSZ and NGSZ), enzyme-linked immunosorbent assay of leaf samples of four species (C. brasilianum, C. pascuorum, C. pubescens and C. macrocarpum) revealed infections of two Potyviruses – Bean common mosaic virus and Cowpea aphid-borne mosaic virus – and three Comoviruses – Cowpea mosaic virus, Cowpea severe mosaic virus and Bean pod mottle virus. Other viruses detected included: a Carmovirus, Cowpea mottle virus; a Cucumovirus, Cucumber mosaic virus (CMV); a Sobemovirus, Southern bean mosaic virus; and a Tobamovirus known as Tobacco mosaic virus (TMV). While no viruses were detected in leaf samples of C. brasilianum and C. pubescens collected from NGSZ, leaf samples of the same species collected from DSZ were highly infected, with the former being infected with seven viruses and the latter with all nine viruses tested for. Seed transmission studies of these viruses in Centrosema species showed CMV to be the most frequently detected, followed by TMV, and four different viruses were found in seeds of C. brasilianum in DSZ. The paper discusses the implications of these results for cropping of Centrosema legumes.